Fungsi Rotasi Siang dan Malam dalam Al-Qur'an:Analisis Tafsir Tematik - Binti Khabibatur RA; Khamim Jazuli (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study examines the function of the Earth’s rotation that results in the alternation of day and night from the perspective of the Qur’an using a thematic interpretative approach. Employing a descriptive qualitative method based on library research, this study relies on Qur’anic verses and Tafsir al-Misbah as primary sources, supported by scientific and astronomical literature. The findings reveal that the phenomenon of day and night in the Qur’an is not merely presented as a natural occurrence, but is understood as encompassing three interrelated functions: spiritual, theological, and pragmatic. These functions collectively reflect the Qur’anic invitation for human beings to contemplate the order of the universe as a manifestation of divine signs, thereby cultivating spiritual awareness and intellectual discernment characteristic of ulil albab.